Intermediate GCSE Mathematics : Revision and practice - Rayner, D. (New York : Oxford University press, 1994)
Provides explanations and examples, supported by many practice exercises and past examination questions that aim to build students' confidence. This title includes: curriculum coverage, non-calculator work in line with curriculum changes, and a section of ideas for longer investigations to encourage students to use and apply the mathematics
Includes index.
Keywords: Mathematics -- Examinations -- Study guides; Mathematics -- Examinations